Contested Maritime Spaces in the Middle East: Geopolitical Dynamics, Non-State Actors, and Security Challenges in the Red Sea and the Strait of Hormuz - Ridha Munawir Masly Pandoe; Rachmat Setiawibawa; Harri Dolli Hutabarat; Guntur Eko Saputro; Lukman Yudho Prakoso (Advances In Social Humanities Research, 2026)
In recent years, these routes have been exposed to multifaceted and hybrid security threats—including missile and drone attacks, deployment of unmanned maritime systems, cyber intrusions, the rise of piracy, and proxy wars waged by non-state actors backed by regional powers. Such developments significantly increase the vulnerability of maritime traffic and pose serious risks to international economic stability and energy security. The study examines how contemporary geopolitical dynamics are shaping maritime security challenges in the Middle East by analyzing recent security incidents, regional power competitions, and the evolving role of international navies operating in the region. Using a qualitative geopolitical security approach, the study draws on policy documents, security reports, and incident analyses to identify the key drivers of maritime insecurity. These findings suggest that maritime instability in the Middle East is driven by the convergence of unresolved regional conflicts, the adoption of asymmetric warfare strategies, and the increasing involvement of external forces seeking to protect strategic interests. This combination has complicated traditional maritime security frameworks and weakened unilateral security measures. Therefore, the study underscores the urgent need for coordinated multilateral maritime governance, enhanced information sharing, and collective security mechanisms to ensure the protection of critical sea lanes and the long-term stability of the regional and global maritime domains.